Social isolation and initiation skills: a longitudinal test of the loneliness model and the buffering effect of cognitive flexibility - Curran, Timothy; Arroyo, Analisa (Frontiers in Communication, 2025)
The Loneliness Model posits that social isolation activates cognitive biases wherein people perceive increased social threats and become less sociable. The longitudinal study reported here tested this theoretical tenet in the context of students transitioning to college. Specifically, we examined the association between social isolation and social skills for initiating new relationships, and also examined how cognitive flexibility could potentially buffer the strength of this direct effect. Participants were recruited at a university orientation in the late summer before the start of their first college semester. They reported their levels of social isolation, initiation skills, and cognitive flexibility in August (T1) and again in January (T2). The results showed that T1 social isolation predicted lower initiation skills at T2 while controlling for initiation skills at T1, thus social isolation predicted lower levels of initiation skills at a later time. Cognitive flexibility also buffered this negative relationship, indicating that cognitive flexibility may serve as a protective factor in the link between social isolation and communication skills. The practical and theoretical implications of these findings are discussed.